Pengajaran penyalahgunaan dadah dalam kalangan pelajar tingkatan empat - Abd Razak, Mohd Noorazam; Mohd Radzi, Fatin Aliana; Adnan, Mohamad Azmi; Ismail, Hasbullah; Mohamed, Ani Mazlina Dewi; Omar Fauzee, Mohd Sofian (Agensi Antidadah Kebangsaan, 2009)
This research examines the effectiveness of drug abuse education in school. Demography variable in terms of academic qualification, parent’s knowledge and family experience that influence the effectiveness of drug abuse education among the form four students at secondary school in Shah Alam, Selangor. The respondents of this study are 80 participants who are basically involved in drug abuse education class. It involves 31 male students and 49 female students. This study is conducted by survey using questionnaire which have four sections as research instruments. Data and information will be evaluated via percentages and frequency only. The findings of the previous study have shown that drug abuse education in this school has its positive contribution towards the drug knowledge among students. More than fifty percent students also agreed that drug education session in school done effectively. Besides that, the findings for this research suggest that parents plays a crucial role in distributing drug abuse information to students compared to other sources. This research also recommends that drug education in school be improved by using variety of teaching and learning techniques by teachers.